Preactional self-regulation as a tool for successful problem solving and learning - Lehmann, T.; Ifenthaler, Dirk (2011)
This study investigates the effect of preactional self-regulation on the quality of problem solving. The experimental study was realized in a problem-based self-regulated learning environment. Data of 78 participants on externalized mental models, re-representing the problem solutions, were collected. A computer based diagnosis and analysis tool was utilized to determine the congruence between the subject's and an expert's solution. This allowed capturing, quantifying and comparing the quality of the participants' problem solution. Results show that an initiated phase of preactional self-regulation leads to a higher quality problem solving. However, findings show no significant differences between experimental groups and the control group.